A kinetic model for actinorhodin production by Streptomyces coelicolor A3(2) - Elibol, M; Mavituna, F (Elsevier Sci Ltd, 1999)
The fermentation kinetics of an extracellular antibiotic, actinorhodin, by Streptomyces coelicolor were studied in a batch system. A simple model was proposed using the Logistic equation for growth, the Luedeking-Piret equation for actinorhodin production and Luedeking-Piret-like equations for glucose and oxygen consumptions. The model appeared to provide a reasonable description for each parameter during the growth phase. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: actinorhodin; Streptomyces coelicolor; kinetic model; logistic equation; Luedeking-Piret equations